Preliminary Investigation: Teachers’ Perception on Computational Thinking Concepts - L. Ling, Ung; C. Saibin, Tammie; Labadin, Jane; Abdul Aziz, Norazila (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
As Computational Thinking (CT) is to be integrated into Malaysian syllabus by the year of 2017, this study therefore is designed to explore Malaysian teachers’ perception on CT. A survey method is employed; questions were constructed based on the Technology Acceptance Model (TAM) to acquire teachers’ perception on CT. 159 teachers from all over Malaysia completed the survey form. Spearman’s Rank Order correlation was implemented on the obtained data. This study managed to present teachers perception on CT via perceived usefulness of CT, perceived ease of CT integration into teaching and learning practices, teachers’ attitude towards CT and their intention to integrate CT into their classroom, their basic understanding on CT and their concern on CT integration. Our investigation shows teachers had a weak understanding of CT, which led to unnecessary concerns related to the CT integration. The results also show strong positive correlation on perceived ease of CT integration with behavioral intention and teachers’ attitude with behavioral intention.